Construct validity test on the Indonesian version of Career Decision-Making Self-Efficacy Scale (CDSES) - P. Tommy Y. S. Suyasa; Jessyca Jessyca; Felita Oktaviani; Amala Fahditia (Jurnal Konseling dan Pendidikan, 2023)
This study aimed to assess the construct validity of Indonesian version of the Career Decision-Making Self-Efficacy Scale (CDSES) by conducting a convergent evidence test. This version comprised 30 items that measured individual confidence in making career-related decision across seven dimensions, including occupational information (OI), goal selection (GS), self-appraisal (SA), school achievement (ScA), problem-solving (PS), social support (SS), and planning. Despite passing the content validity test, CDSES-Indonesian version lacked psychometric properties in terms of convergent evidence. A construct validation analysis was carried out, incorporating the NEO-PI instruments developed by Costa & McCrae in 1992 into CDSES-Indonesia version. This study involved 211 respondents, including 123 women and 88 men aged between 17 and 35, all being university students. Google Form was used as a platform to distribute the questionnaires for the two measuring instruments to the participants. The results showed a significant relationship between CDSES and personality traits. Four personality traits, namely conscientiousness, openness, extraversion, and agreeableness, exhibited positive correlations with CDSES, while neuroticism showed a negative relationship.